2010
DOI: 10.1242/jcs.061879
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of the extracellular-Ca2+-sensing receptor in mouse taste cells

Abstract: SummaryThree types of morphologically and functionally distinct taste cells operate in the mammalian taste bud. We demonstrate here the expression of two G-protein-coupled receptors from the family C, CASR and GPRC6A, in the taste tissue and identify transcripts for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 83 publications
(107 reference statements)
2
43
0
Order By: Relevance
“…Previous studies have described the expression of this receptor in different tissues and cells e.g. soft palate, liver, blood vessels and taste cells (Kuang et al 2005;Wellendorph et al 2007;Harno et al 2008;Bystrova et al 2010). As all identified endogenous agonists for family C receptors are nutrient-like molecules reaching from ions and sugars to amino acids (Quiocho and Ledvina 1996;Wellendorph et al 2009a;Geraedts et al 2010), the broadly tuned L-amino-acid receptor GPRC6A presents a plausible candidate for being a nutrient sensor of emerging physiological significance (Kuang et al 2005;Wellendorph et al 2007;Wellendorph et al 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have described the expression of this receptor in different tissues and cells e.g. soft palate, liver, blood vessels and taste cells (Kuang et al 2005;Wellendorph et al 2007;Harno et al 2008;Bystrova et al 2010). As all identified endogenous agonists for family C receptors are nutrient-like molecules reaching from ions and sugars to amino acids (Quiocho and Ledvina 1996;Wellendorph et al 2009a;Geraedts et al 2010), the broadly tuned L-amino-acid receptor GPRC6A presents a plausible candidate for being a nutrient sensor of emerging physiological significance (Kuang et al 2005;Wellendorph et al 2007;Wellendorph et al 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…As was mentioned above, TRPM5 are the key elements of the cascade of taste transduction functioning in type-II taste cells specialized in the recognition of bitter, sweet, and umami stimuli. Using electrophysiological criteria that we proposed earlier, the type-II cells can be identified rather unambiguously [9,13,14]. We showed that nonselective ion channels, which resemble, by their kinetics of activation and the property of outward rectification, the recombinant TRPM5, do exist in these cells.…”
mentioning
confidence: 60%
“…6C). We found that this effect is related to the functioning of calciumsensitive receptors (CaSRs), i.e., receptors associated with G protein belonging to the C family, in cells of this type [17]. These receptors can be activated by nearly all L-amino acids, but they demonstrate maximum sensitivity to phenylalanine and minimum sensitivity to arginine (D).…”
Section: Resultsmentioning
confidence: 99%
“…For synthesis of the first chain of cDNA with RNA of the matrix, we used reverse transcriptase SuperScriptIII (Invitrogen, USA) and oligo(dT) primer. To amplify specific parts of cDNA of the corresponding receptors with the help of PCR, we used pairs of gene-specific primers [2,11,[14][15][16][17] constructed based on the corresponding nucleotide sequence from the GenBank databases.…”
Section: Methodsmentioning
confidence: 99%